RELEVANCE OF FORENSIC ACCOUNTING PROFESSIONAL CERTIFICATIONS ON FRAUD REDUCTION IN NIGERIAN DEPOSIT MONEY BANKS - Kamaluddeen Funsho Adisa IBRAHIM (Malete Journal of Accounting and Finance)
This study examines the relevance of forensic accounting professional certifications on fraud reduction in Nigerian deposit money banks. The study is based on ex post facto and survey research designs. Data was collected through primary and secondary sources. Analysis of secondary data was done using Ordinary Least Square (OLS) regression technique which further necessitated correction of the problem of autocorrelation via Generalized Least Square regression. Bootstrapping estimation procedure was also carried out to confirm the regression results from the tested hypothesis. Analysis of primary data was undertaken, using One-way ANOVA. The results from the findings based on the bootstrapping estimation method clearly suggest that increasing the engagement of forensic accountants’ significantly reduces the incidence of fraud in deposit money banks in Nigeria. The results further reveal significance difference in practitioners’ perceptions on the relevance of forensic accounting certification criteria to fraud reduction in Nigeria which successfully meets the body of knowledge, ethical code of conduct and protection of public interest conditions but fails to adequately fulfil the control of entry requirement. Consequently, the study recommends, among other policy options, more awareness campaign by professional bodies to educate regulatory authorities on constant utilisation of forensic accounting services.